Diterpenoids and sesquiterpenoids from the stem bark of Metasequoia glyptostroboides. (May 2019) - Tu, Wen-Chao; Qi, Yan-Yan; Ding, Lin-Fen; Yang, Hui; Liu, Jiang-Xin; Peng, Li-Yan; Song, Liu-Dong; Gong, Xun; Wu, Xing-De; Zhao, Qin-Shi
Abstract: A phytochemical study on the stem bark of Metasequoia glyptostroboides led to the isolation of sixty-one diterpenoids and sesquiterpenoids, including seventeen previously undescribed compounds, metaglyptins A-Q. Their structures were elucidated by extensive analysis of spectroscopic data (IR, UV, HRESIMS, and 1 H, 13 C and 2D NMR). The absolute configurations of metaglyptins I, J, and O were determined by the ECD data and single-crystal X-ray diffraction analysis. The undescribed compounds were evaluated for their cytotoxicity against HeLa, AGS, and MDA-MB-231 cancer cell lines. The results revealed that metaglyptin A exhibited moderate cytotoxicity against MDA-MB-231 cell line with IC50 value of 20.02 μ M. Graphical abstract: Seventeen previously undescribed diterpenoids and sesquiterpenoids, as well as forty-four known compounds, were isolated and structurally characterized from the stem bark of Metasequoia glyptostroboides . The isolated undescribed compounds were evaluated for their cytotoxic activity.Image 1 Highlights: Seventeen undescribed terpenoids were isolated from Metasequoia glyptostroboides. Forty-four known diterpenoids and sesquiterpenoids were isolated. Metaglyptin A exhibited moderate cytotoxicity against MDA-MB-231 cell line.